The Endophyte Pantoea alhagi NX-11 Alleviates Salt Stress Damage to Rice Seedlings by Secreting Exopolysaccharides - Sun, Liang; Lei, Peng; Wang, Qian; Ma, Junjie; Zhan, Yijing; Jiang, Kang; Xu, Zongqi; Xu, Hong (Frontiers in Microbiology, 2020)
Endophytes have the potential to enhance the ability of plants to resist salt stress, improving crop development and yield. Therefore, in this study, we isolated an endophyte that produced large amounts of exopolysaccharides (EPSs) from the roots of sea rice and examined its effects on the physiological responses of rice (Oryza sativa L. ssp. japonica ‘Nipponbare’) seedlings to salt stress using hydroponic experiments. The endophyte was named Pantoea alhagi NX-11 based on its morphological characteristics and 16S ribosomal DNA (rDNA) sequence alignment. Rice seedlings that had been inoculated with P. alhagi NX-11 exhibited a 30.3% increase in fresh weight, a 28.6% increase in root length, a 51.6% increase in shoot length, and a 26.3% increase in chlorophyll content compared with control seedlings under normal conditions. In addition, inoculated rice seedlings had a 37.5% lower malondialdehyde content, a 133% higher K+/Na+ ratio, and a 52.8% higher proline content after 7 days under salt stress, as well as up-regulated expression of proline synthase, down-regulated expression of proline dehydrogenase, and enhanced antioxidant enzyme activities. Interestingly, rice seedlings that were inoculated with an EPS-deficient strain named NX-11eps− that was obtained by atmospheric and room temperature plasma (ARTP) mutagenesis were damaged by salt stress and had similar physiological and biochemical indicators to the control group. Therefore, we speculate that the ability of P. alhagi NX-11 to enhance the salt tolerance of rice seedlings is related to the EPSs it produces.